Guided Inquiry Learning Model in Science Learning on Responsible Attitudes of Elementary School Students - Hamid, Sundari; Muhammad Yunus; Ifa Safira; Satria; Tismi Dipalaya (MIMBAR PGSD Undiksha, 2023)
The lack of students' responsible attitudes towards science subjects means that teachers must be able to design meaningful learning and maximize student involvement in the learning process, therefore the guided inquiry learning model is an alternative for trying to increase students' responsible attitudes in the learning process. This research was carried out with the aim of analyzing the effect of implementing the guided inquiry learning model on the responsible attitudes of fifth grade elementary school students. This type of research is quasi-experimental research using non-equivalent control group design. The population was 56 students so a total sampling of 56 students was used. The data in this study was collected using observation sheets and questionnaires, then analyzed using the SPSS version 20 program, data analysis consisted of normality tests, homogeneity tests, and paired sample T-tests. The results of the research are that there is a significant influence on the application of the guided inquiry learning model on the responsible attitude of fifth grade elementary school students in science subjects. It was concluded that the application of the guided inquiry learning model could improve the responsible attitude of fifth grade elementary school students in science subjects.